ANGIELSKI SZANSĄ DLA FRANCUSKIEGO, CZYLI REFLEKSJA O ZINTEGROWANYM NAUCZANIU JĘZYKOWYM Z PERSPEKTYWY DYDAKTYKI WIELOJĘZYCZNOŚCI - Piotrowska-Skrzypek, Małgorzata (Neofilolog, 2018)
The supporters of the concept of multilingualism and interculturalism emphasize that learning new languages is more effective when one consciously refers to the past and current experiences in the exploration and use of languages. A person who, in addition to the mother tongue, learned a foreign language and knows how to use it, not only possesses a skill set needed in the process of learning but also has the information about a language system. Referring to the available research on multilingualism, this article outlines the methods of utilizing this potential during foreign language classes and of preparing the ground for a complex program of teaching additional languages.